Methanogenic archaea from Siberian permafrost: fit for Mars? - Morozova, Daria; Wagner, Dirk (2005)
Evolution of Life on Earth started 3.5 Ga ago, when living conditions on Mars were similar to those on early Earth. Hence it is legitimate to assume that life emerged on Mars as well as on early Earth. Current ESA mission Mars Express determined water on Mars, fundamental requirement for life, and presence of CH4 in the Martian atmosphere, which could be originated only from active volcanism or from biological sources. This finding implicates that microbial life could still exist on Mars. One possibility for survival of Martian primitive life might be subsurface lithoautotrophic ecosystems. Comparable environments exist in permafrost regions on Earth.Despite the unfavourable life conditions, permafrost is colonized by high numbers of viable microorganisms, including methanogenic archaea. The capability of these organisms to grow under lithoautotrophic conditions, whereby energy is gained by the oxidation of H2 and CO2 is the only carbon source under strictly anaerobic conditions, tolerance to low temperatures and long-term survival under extreme conditions of permafrost make methanogens to the most suitable keystone organism for the investigation of possible Martian life.Within the scope of DFG Priority Program Mars and the Terrestrial Planets we study the tolerances of methanogens under extreme life conditions of terrestrial or extraterrestrial permafrost (Mars simulation). The borders of growth influenced by desiccation, temperature extremes, radiation and high salt concentration were analyzed for the methanogenic archaea in pure cultures as well as in their natural environment of Siberian permafrost. First results represent high survival potential under these extreme conditions. Significant CH4 formation appeared even by incubation with saturated salt solution (0.02 nmol CH4 h-1 g-1), radiation dose 5000 Jm-2 (0.8 nmol CH4 h-1 g-1), desiccation (13.06 nmol CH4 h-1 ml-1) and subzero temperatures (0.04 nmol CH4 h-1 ml-1).